Longarm and the Durango Payroll - Evans, Tabor (New York Jove Books, 1985)
The gang that robbed the Durango bank and rode off with the miners payroll was wiped out to the last man by a band of hostile Indians. But the money wasn't lost. It was stashed in the grave of an Indian chief. U.S. Marshal Long has orders to dig up the money, and he doesn't need vigilantes, frisky beauties or hired guns to tell him whose grave he's digging.
Keywords: Novel